1985
DOI: 10.1515/botm.1985.28.6.259
|View full text |Cite
|
Sign up to set email alerts
|

Lignicolous Marine Fungi in a Harbour Environment (Milazzo)

Abstract: The occurrence and distribution of marine lignicoious fungi in the inner area of Milazzo harbour (Messina) were investigated. Marine fungi belonging to the Ascomycotina, Deuteromycotina and Basidiomycotina, occurring on panels of Pinus sylvestris, Fagus sylvatica and Populus sp. were identified. The total number of fungal occurrences was 254 belonging to 16 species (13 genera). The most common fungi found were Corollospora maritima, Lulworthia sp., Remispora maritima (Ascomycotina) and Cirrenalia macrocephala … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…These include Halosphaeria appendiculata, Arenariomyces trifurcatus, Nia vibrissa, Papulospora halima and Humicola alopallonella. Cirrenalia macrocephala, on the other hand, was found more frequently on pine and this confirms the observations of other workers (Grass0 et al, 1985;Jones, 1976). Beech, pine and poplar appear to be the timbers most frequently used in field studies, although Furtado & Jones (1980) and Suhirman & Jones (1984) have also investigated the colonization of tropical timbers by marine fungi.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These include Halosphaeria appendiculata, Arenariomyces trifurcatus, Nia vibrissa, Papulospora halima and Humicola alopallonella. Cirrenalia macrocephala, on the other hand, was found more frequently on pine and this confirms the observations of other workers (Grass0 et al, 1985;Jones, 1976). Beech, pine and poplar appear to be the timbers most frequently used in field studies, although Furtado & Jones (1980) and Suhirman & Jones (1984) have also investigated the colonization of tropical timbers by marine fungi.…”
Section: Discussionsupporting
confidence: 91%
“…The community reported for the Straits of Messina is related to that listed by Grass0 et al (1985) for Milazzo, Sicily. Fungi not collected at Milazzo include : Lignincola laevis, Nereiospora comata, Ceriosporopsis circumvestita and Papulaspora halima.…”
Section: Discussionmentioning
confidence: 98%
“…Initialy this was focused on temperate water fungi, especially wood-inhabiting taxa (Jones 1968;Schaumann 1968Schaumann , 1969Schaumann , 1975Grasso et al 1985Grasso et al , 1990Cuomo et al 1985Cuomo et al , 1988Shearer and Burgos 1987) with fewer studies in more recent years (Petersen and Koch 1997;Panebianco et al 2002;Abdel-Wahab 2011a, b). The most intensive collections were made by Koch and Petersen (1996), Lintott and Lintott (2002), Jones et al (1998), Jones (2010) and AbdelWahab et al 2008 who reported 75 (Denmark), 38 (New Zealand), 92 (Friday Harbour, USA) and 41 (Italy) fungi, respectively.…”
Section: Lignicolous Marine Fungimentioning
confidence: 99%
“…drift material and entrapped wood Koch and Petersen 1996;Jones et al 1998;Lintott and Lintott 2002), sampling of fixed structures (Koch and Petersen 1996) or wood panels submerged in the sea (Miller et al 1985;Panebianco et al 2002). Ceriosporopsis halima, Cirrenalia macrocephala, Corollospora maritima, Halosphaeria appendiculata, Halosphaeriopsis mediosetigera, Lulworthia spp., Marinospora calyptrata, Monodictys pelagica, Remispora maritima, R. stellata, Torpedospora radiata, and Zalerion maritima can all be regarded as common lignicolous species in temperate waters (Hughes 1969;Byrne and Jones 1974;Grasso et al 1985;Jones 1985;Cuomo et al 1988;Petersen and Koch 1997). Most are members of the Halosphaeriales while very few bitunicate ascomycetes are to be found on submerged wood (Jones 1985).…”
Section: Lignicolous Marine Fungimentioning
confidence: 99%
See 1 more Smart Citation